Controle judicial de políticas públicas: fundamentos, limites e consequências - Cardoso, Diego Brito (2017)
In the last three decades Brazil has witnessed an expansion of the judiciary's role in the realization of fundamental rights and in the control of the Executive and Legislative omissions. Indeed, in the legal and political scenario experienced in the country after the 1988 Federal Constitution, the judicial control of public policies has gained more space. In this context, the present research seeks to investigate what is called the "public policies", through the study of its formation procedures and its elements, in order to establish basic concepts for the study of this theme. The present study deals with the main justifications for judicial control practiced in Brazil, demonstrating, in the end, the jurisprudential evolution related to the subject, since the promulgation of the Magna Carta of 1988. Based on several authors, many of them with possibly disparate views on the subject, the study presents three limits to the judicial control of policies, avoiding some of the traditional claims related to separation of powers, to the administrative discretion and the principle of legality, always with the objective of compliance with the duty to reduce social inequalities and respect for the principle of material equality. Finally, aware that judicial control of public policies can generate positive and negative externalities for the society, the present study makes a critical analysis of the subject, demonstrating the possible consequences of a greater or lesser control of public policies by the Brazilian Judiciary